Faktor – Faktor Yang Mempengaruhi Kebijakan Hutang Perusahaan Manufaktur Yang Terdaftar Di Bei - Cynthia Angela, Yanti (Jurnal Paradigma Akuntansi, 2019)
The purpose of this study is examine the analysis of factors affceting debt policy of manufacture companies listed on Indonesia Stock Exchange for the period 2015-2017. Sample was selected using purposive sampling method amounted to 34 companies. Data processing techniques using multiple regression analysis what helped by Eviews 9.0 and Microsoft Excel 2010. The result of this study shows that partially institutional ownership and liquidity have significant effect on debt policy, while managerial ownership and profitability have no significant effect on debt policy. However this study shows that simultaneously institutional ownership, managerial ownership, profitability, and liquidity have a significant effect on debt policy.